2008
DOI: 10.2514/1.26134
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Models Assessment for Large-Scale Tip Vortices in an Axial Compressor Rotor

Abstract: Six turbulence models frequently used in compressor aerodynamics were employed in the detailed numerical investigations of a low-speed large-scale axial compressor rotor, for which the tip flows were measured in detail with stereoscopic particle image velocimetry, to assess the predictive capabilities of the turbulence models for large-scale vortices in the tip region of the rotor. The six turbulence models include: the mixing-length model, the SpalartAllmaras model, the standard k " model, the shear-stress tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Hence, we try to take account of the energy backscatter in turbulence models with helicity based on the above results. It is generally accepted that no single turbulence model is universally superior for all classes of problems in compressors [11,12]. Three-dimensional separations have been identified as an inherent flow feature of the corner formed by the blade suction surface and endwall of axial compressors (as shown in Fig.…”
Section: Modification Of Spalart-allmaras Model Using Velocity Helicitymentioning
confidence: 99%
“…Hence, we try to take account of the energy backscatter in turbulence models with helicity based on the above results. It is generally accepted that no single turbulence model is universally superior for all classes of problems in compressors [11,12]. Three-dimensional separations have been identified as an inherent flow feature of the corner formed by the blade suction surface and endwall of axial compressors (as shown in Fig.…”
Section: Modification Of Spalart-allmaras Model Using Velocity Helicitymentioning
confidence: 99%
“…This was observed by Yaras and Sjolander [9] using three-hole probe measurements inside the tip gap, by Palafox et al [10] using PIV measurement and by Krishnababu et al [11] using numerical methods. Liu et al [13] assessd different turbulence models for the predction of tip leakage vortex. Most studies observed a reduction of tip leakage mass flow rate due to endwall motion.…”
Section: Introductionmentioning
confidence: 99%
“…The equations solved are the fully three-dimensional, compressible, Reynolds averaged, Navier-Stokes equations. Six different turbulence models frequently used in compressor aerodynamics, namely the mixinglength model, the Spalart-Allmaras model, the standard k-ω model, the SST k-ω model, the 2 v -f model, and the Reynolds stress model were employed as detailed in the numerical investigation of Liu and Liu (2008). The results showed that none of them exhibited absolute superiority for the prediction of the complex turbomachinery flow.…”
Section: Calculation Modelmentioning
confidence: 99%